Strain rate-independent growth of the deformation twin in a CrMnFeCoNi high-entropy alloy - Shipan Yin; Fan Zhang; Jingyao He; Zeyu Meng; Zezhou Li; Xingwang Cheng (Materials Research Letters)
Growth characteristics of deformation twins are investigated in a CrMnFeCoNi alloy. Irrespective of grain size and strain rate, the twins assume a special morphology of extremely thin lamellae with an average thickness of ∼4.0 nm. The twin lamellae run through a whole grain and twin thickness only increases slightly, indicating that twin thickening is difficult. Increasing the volume fraction of deformation twins is mainly achieved by the accumulation of thin twins with an increasing strain rate. Moreover, twin fronts are invariably composed of cooperative Shockley partial dislocations with minimized Burgers vector, which could be taken into account for the strain rate-independent twin growth under certain conditions.